Caracterização e análise ambiental do Campus da Universidade Federal de São Carlos (UFSCar), São Carlos, SP - Paese, Adriana (1997)
It was made an environmental characterization as a preliminar basis for the environmental planning and land ocupation strategies, at the Federal University of São Carlos’s campus (São Carlos, SP), through its structural variables conversion (hidrology, altimetry, land use patterns, vegetation cover) to digital format, using GIS-IDRISI. The resulting thematic maps, besides gathering important information which can subside the development of other studies, allowed the landscape units (biotopes) identification. The biotopes spatial patterns suggest different proposals for the urbanized and not urbanized areas